LIABILITY FOR THE CRIMINAL ACT OF RAPE ON A MINOR BY DECEPTION BASED ON JUDGMENT NO. 11/PID. SUS ANAK/2022/PN TJK - Gumilang, M. Adhitya Ridho; Ramasari, Risti Dwi; Wayka, Gindha Ansori (Institut Agama Islam Negeri Bone, 2023)
ABSTRACTSexual violence that occurs at this time, especially the rape of women and children is increasingly prevalent, making the community very restless. In fact, this also happens to underage teenagers who are still in school, which should focus on education. The purpose of this paper is to determine the responsibility of the perpetrators of committing the crime of Rape on Minors by Deception. This writing uses a normative juridical approach research method and qualitative descriptive research. Criminal liability is based on several elements, namely the presence of each person. This element is intended to further examine who is sitting as a child, whether it is really the culprit or not, this is to avoid an error in persona in punishing someone. In this case, a child has been brought before the trial, namely, the child is in good physical and mental health and is able to answer all questions that are asked to him clearly and responsively, then there is an element of deliberately tricking, a series of lies, or persuading the child to have intercourse with him. or with other people.Â